Assessment of the visual aesthetic quality of the urban landscape in the Tabriz metropolis - Sonia Sarafraz Asbagh; Hassan Mahmoudzadeh; Asa Ode Sang (Sustainable Earth Trends)
To improve human well-being, there is a growing awareness of enhancing aesthetic benefits through landscape design, planning and management. Monitoring long-term changes can play a significant role in the direction of urban management. This study aims to visually evaluate the aesthetic quality of the Tabriz metropolis landscape and monitor changes in Landscape Aesthetic Quality (LAQ). LAQ is as-sessed based on visual scale, naturalness, stewardship, historicity, complexity, disturbance, ephemera, and imageability. Using multiple temporal satellite images and landscape metrics, we analyze land use changes between 1984 and 2020. The results reveal that urbanization has led to landscape fragmentation and loss of coherence over the past three decades. Additionally, we calculate the weights of the criteria using the CRITIC method, highlighting the changing importance of different factors. The results are historicity with a coefficient of 0.22, naturalness 0.15, Disturbance 0.14, and coherence. 0.14, ephemera 0.13, complexity 0.11, and visual scale 0.11 in 1984. For the year 2020, the coefficient for historicity is 0.13, naturalness is 0.18, disturbance is 0.11, coherence is 0.10, ephemera is 0.10, complexity is 0.12, and visual scale is 0.26 Historicity and naturalness hold the greatest weights in 1984, while visual scale and naturalness receive the highest weights in 2020. Significant changes are observed in districts 9 and 1, while districts 7 and 6 show minor adjustments. The findings provide valuable insights for improving ecological networks in future urban planning in Tabriz. Urban management should consider these calculations to enhance the LAQ index.